Risk factors for dietary deficiency and their probable role in elderly morbidities: a cross sectional study among elderly residing in rural field practice areas of S.N. Medical College, Bagalkot, North Karnataka - Desai, Sachin; Agarwal, Sidharth; Mannapur, B. S.; Dorle, A. S. (International Journal Of Community Medicine And Public Health, 2018)
Background:Nutrition is an important element of health, among the elderly. They are prone for dietary deficiencies and thus suffer from a plethora of nutritional deficiency disorders due to various factors, prevalent from region to region. Estimating the risk factors for nutritional deficiencies, dietary patterns and their role in elderly morbidities is of utmost importance. Methods:140 Elderly, with the help from their caregivers, were screened for nutritional deficiencies by a detailed general physical examination and for signs of nutritional deficiencies namely: water soluble B-complex vitamins. Elderly were examined for the anthropometric measurements like height, weight, BMI, mid arm circumference, calf circumference and nutritional deficiency disorders. Elderly malnutrition was assessed using mini nutritional assessment (MNA)scale score, body mass index (BMI)and weight loss >10% of body weight. Results:Of the total elderly, 45 (32.1%) of elderly are underweight and 42 (30.0%) of elderly were obese. 63 (45%) each, had a waist hip ratio value of >0.95 in men and >0.85 in women. 69 (49.3%) of the elderly were having a Mid-arm circumference of <24 centimeters. 1 (43.6 %) elderly, was having 12-14 points (normal nutritional status) 76 (54.3 %) had a score of 8-11 points i.e. at risk of Malnutrition 03 (2.1%) had a score between 0-7 patients were malnourished. Conclusions: Dietary patterns of the elderly decreases with age and is affected by multiple determinants like psychosocial stress, dementia, delirium, poor economic status, poor dentition, chronic debilitating illnesses, smoking and alcohol, which play a vital role in elderly malnutrition.